2015
DOI: 10.17576/jsm-2015-4403-01
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the White-rot Fungus, Trametes menziesiifor Landfill Leachate Treatment

Abstract: The study monitored

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Therefore, the search for innovative and sustainable technologies to reduce the impact of untreated leachate is a serious environmental concern (Jones et al, 2006;Ghosh et al, 2014b). Although the composition of LFL varies widely, depending on diverse factors including age and degree of stabilization of waste, several common features can be observed (Umar et al, 2010;Razarinah et al, 2015), such as the presence of high ammonia concentrations, high organic loads, and the presence of inorganic compounds, including heavy metals and salts (Kamaruddin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the search for innovative and sustainable technologies to reduce the impact of untreated leachate is a serious environmental concern (Jones et al, 2006;Ghosh et al, 2014b). Although the composition of LFL varies widely, depending on diverse factors including age and degree of stabilization of waste, several common features can be observed (Umar et al, 2010;Razarinah et al, 2015), such as the presence of high ammonia concentrations, high organic loads, and the presence of inorganic compounds, including heavy metals and salts (Kamaruddin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The movement of LFL into the surrounding soil, ground water, or surface water, may lead to severe pollution (Razarinah et al, 2015;Kumari et al, 2016) and thus regulations concerning LFL discharge into receiving waters are becoming more and more stringent (Renou et al, 2008;Peyravi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to the fact that many high-molecular-weight compounds fail to penetrate the cell membrane and are also not altered by extracellular enzymes [68]. The screening of fungi for their ability to grow on landfill leachate incorporated with MEA has previously been studied by Razarinah et al [69]. These authors showed that the highest growth rate was recorded for Ganoderma australe, Trametes menziesii (KUM 7011(54)) and Penicillium sp on MEA containing 100% of landfill leachate.…”
Section: Screening On Solid State Culturementioning
confidence: 99%
“…It is estimated that the total volume of leachate generated from landfills in Malaysia is about 3 million liter/ day, and the quantity of leachate is often more in some countries due to heavy rainfall as Malaysia (Agamuthu et al 2011). Leachate produced from the interaction of wastes and rainfall also contains trace amounts of chemical pollutants, heavy metals, dissolved and colloidal solids and various pathogens that can potentially contaminate groundwater and surface water (Ashraf et al 2019;Razarinah et al 2015;Tzoupanos & Zouboulis 2009). Several factors affecting the characteristics of leachate such as collection system of solid waste, the age of the landfill which that reflect on the stabilization of the waste, the type and composition of the discarded waste, the ability of solid waste component to be dissolved, site and hydrological factors, solid waste compaction, as well as landfill design and operations (Jeeva & Umar 2012;Salem et al 2008;Weng et al 2011).…”
Section: Introductionmentioning
confidence: 99%